American grown : - Obama, Michelle (Crown Publishers, 2012)
Now, in her first-ever book, American Grown, Mrs. Obama invites you inside the White House Kitchen Garden and shares its inspiring story, from the first planting to the latest harvest. Hear about her worries as a novice gardener – would the new plants even grow? Learn about her struggles and her joys as lettuce, corn, tomatoes, collards and kale, sweet potatoes and rhubarb flourished in the freshly tilled soil. Get an unprecedented behind-the-scenes look at every season of the garden’s growth, with striking original photographs that bring its story to life. Try the unique recipes created by White House chefs and made with ingredients just picked from the White House garden. And learn from the White House Garden team about how you can help plant your own backyard, school or community garden.